PENINGKATAN KOMPETENSI KOGNITIF FISIKA SISWA MENGGUNAKAN PENDEKATAN OPEN ENDED DENGAN METODE PENEMUAN TERBIMBING DI KELAS XI SMA NEGERI 1 ULAKAN TAPAKIS - Dasmita, Dasmita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The problem of this research were low students’ cognitive competences; Lack of students’ participations, and low students’ ability in expressing their ideas, and also the students’ unwillingness to take part in practical laboratory activities. Thus, the leaning activities only focused on teacher centered and not given enough responses by the students. As a result, the students became passive learners. To overcome such problems, the researcher interested to conduct a research by using Open-Ended and Guided Discovery Methods on Physics subject at grade X of SMA Negeri 1 Ulakan Tapakis in order to improve the students’ ability in learning. The type of this research was a classroom action research. The research conducted on grade X of SMA Negeri 1 Ulakan Tapakis on academic year of 2018-2019. The subject of this research was class X-2 with a total sample of 30 students. The research was done in two cycles. Each cycle consists of planning, implementation, observation and reflection. The data of this research were students’ cognitive. The instrumentation used were observation sheets and field notes. The technique of analyzing data used was descriptive analysis. The results of the research were shown that the students’ cognitive competence was improved from 46.67% on first cycle to 83.33% on second cycle. The research shown that the total improvement on cognitive competences at the end of the second cycle was 36.66%. In brief, the research proved that Open-Ended and Guided Discovery methods were significantly improved the students’ competences in learning Physic.